Does external pneumatic compression treatment between bouts of overreaching resistance training sessions exert differential effects on molecular signaling and performance-related variables compared to passive recovery? An exploratory study. - Cody T Haun; Michael D Roberts; Matthew A Romero; Shelby C Osburn; Christopher B Mobley; Richard G Anderson; Michael D Goodlett; David D Pascoe; Jeffrey S Martin (PLoS ONE)
Purpose We sought to compare the effects of external pneumatic compression (EPC) and sham when used concurrently with resistance training on performance-related outcomes and molecular measures related to recovery. Methods Twenty (N = 20) resistance-trained male participants (aged 21.6±2.4 years) were randomized to balanced sham or EPC intervention groups. The protocol consisted of 3 consecutive days of heavy, voluminous back squat exercise followed by EPC/sham treatment (Days2-4) and 3 consecutive days of recovery (Days5-7) with EPC/sham only on Days5-6. On Day1 (PRE), and Days3-7, venipuncture, flexibility and pressure-to-pain threshold (PPT) measures were performed. Vastsus lateralis muscle tissue was biopsied at PRE, 1-h post-EPC/sham treatment on Day2 (POST1) and 24-h post-EPC/sham treatment on Day7 (POST2). Isokinetic peak torque was assessed at PRE and POST2. Results Peak isokinetic strength did not change from PRE to POST2 in either group. The PPT was significantly lower on Days3-6 with sham, indicating greater muscle soreness, though this was largely abolished in the EPC group. A significant decrease in flexibility with sham was observed on Day3 (+16.2±4.6% knee joint angle; P<0.01) whereas there was no change with EPC (+2.8±3.8%; P>0.01). Vastus lateralis poly-ubiquitinated proteins significantly increased at the POST2 time point relative to PRE with sham (+66.6±24.6%; P<0.025) and were significantly greater (P<0.025) than those observed with EPC at the same time point (-18.6±8.5%). 4-hydroxynonenal values were significantly lower at POST2 relative to PRE with EPC (-16.2±5.6%; P<0.025) and were significantly lower (P<0.025) than those observed with sham at the same time point (+11.8±5.9%). Conclusion EPC mitigated a reduction in flexibility and PPT that occurred with sham. Moreover, EPC reduced select skeletal muscle oxidative stress and proteolysis markers during recovery from heavy resistance exercise.